2016
DOI: 10.1016/j.sysconle.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Output error minimizing back and forth nudging method for initial state recovery

Abstract: This is the preprint version of the article. The final, published version is available on the journal's websiteInternational audienceWe show that for linear dynamical systems with skew-adjoint generators, the initial state estimate given by the back and forth nudging method with colocated feedback, converges to the minimizer of the discrepancy between the measured and simulated outputs — given that the observer gains are chosen suitably and the system is exactly observable. If the system's generator A is essen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…This strategy is generally known as back and forth nudging (BFN), and it was originally proposed by Auroux and Blum in [3] and [4]. A more rigorous treatment was carried out by Ramdani et al in [33] and further studies include [19] by Haine, [20] by Haine and Ramdani, [18] by Fridman, and [1] by Aalto. In [1] it is shown that the initial state estimate given by the BFN method converges to the minimizer of the L 2 -norm of the output discrepancy if the observer gains are taken to zero with a suitable rate.…”
Section: Background and Preliminary Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This strategy is generally known as back and forth nudging (BFN), and it was originally proposed by Auroux and Blum in [3] and [4]. A more rigorous treatment was carried out by Ramdani et al in [33] and further studies include [19] by Haine, [20] by Haine and Ramdani, [18] by Fridman, and [1] by Aalto. In [1] it is shown that the initial state estimate given by the BFN method converges to the minimizer of the L 2 -norm of the output discrepancy if the observer gains are taken to zero with a suitable rate.…”
Section: Background and Preliminary Resultsmentioning
confidence: 99%
“…The main result of [33] is that if there are no noises, that is, η, ν = 0 in (2.1), and if the system is both forward and backward stabilizable, that is, there exist forward and backward feedback operators K ± such that A − K + C and −A − K − C are exponentially stable, then the initial state estimate given by the BFN method converges exponentially to the true initial state of (2.1). The main result of [1] is concerned with colocated feedback K ± j = κ j C * , and it states that if A is skew-adjoint and the system is exactly observable at time T , then assuming that the observer gains satisfy ∞ j=1 κ j = ∞ and ∞ j=1 κ 2 j < ∞, then the initial state estimate converges to the minimizer of the cost function…”
Section: Background and Preliminary Resultsmentioning
confidence: 99%
See 3 more Smart Citations